Writing in Time : Emily Dickinson's Master Hours - Werner, Marta L., 1964- (Book collections on Project MUSE., 2021)
For more than half a century, the story of Emily Dickinson's "Master" documents has been the largely biographical tale of three letters to an unidentified individual. Writing in Time seeks to tell a different story--the story of the documents themselves. Rather than presenting the "Master" documents as quarantined from Dickinson's larger scene of textual production, Marta Werner's innovative new edition proposes reading them next to Dickinson's other major textual experiment in the years between ca. 1858-1861: the Fascicles. In both, Dickinson can be seen testing the limits of address and genre in order to escape bibliographical determination and the very coordinates of "mastery" itself. A major event in Dickinson scholarship, Writing in Time: Emily Dickinson's Master Hours proposes new constellations of Dickinson's work as well as exciting new methodologies for textual scholarship as an act of "intimate editorial investigation."